2008
DOI: 10.3844/ajidsp.2008.85.91
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Region of Dengue Virus Nonstructural Protein 1 Is Involved in Endothelial Cell Cross-Reactivity via Molecular Mimicry

Abstract: Infection with dengue virus (DV) causes diseases ranging from self-limited dengue fever to life-threatening dengue hemorrhagic fever and dengue shock syndrome. Vascular leakage, thrombocytopenia and bleeding are the clinical manifestations associated with dengue hemorrhage. We previously showed that anti-DV nonstructural protein 1 (NS1) antibodies (Abs) cross-reacted with endothelial cells. The potential target proteins on endothelial cell surface recognized by anti-DV NS1 Abs showed sequence homology with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
(49 reference statements)
1
14
0
2
Order By: Relevance
“…There was no significant difference in both IgM and IgG titers of anti-P311-330 and anti-NS1 between different collection days (Supplemental Figure 3). Furthermore, consistent with our previous finding using a different source of patient sera, 42 the percentage of endothelial cells reactive with patient serum IgM correlated with anti-P311-330 IgM titers ( Figure 3C).…”
Section: Resultssupporting
confidence: 92%
“…There was no significant difference in both IgM and IgG titers of anti-P311-330 and anti-NS1 between different collection days (Supplemental Figure 3). Furthermore, consistent with our previous finding using a different source of patient sera, 42 the percentage of endothelial cells reactive with patient serum IgM correlated with anti-P311-330 IgM titers ( Figure 3C).…”
Section: Resultssupporting
confidence: 92%
“…Using sequence homology alignment, we found that the C-terminal region of DV NS1 protein contains cross-reactive epitopes with selfAgs (30,31). To explore the pathological role of cross-reactive epitopes in the hemorrhagic syndrome, we deleted the C-terminal region of DV NS1 protein to generate ⌬C NS1.…”
Section: Nfection With Dengue Viruses (Dv)mentioning
confidence: 99%
“…We previously found that anti-DV NS1 Abs cross-reacted with platelets and endothelial cells (21,22,34), and the C-terminal region of DV NS1 protein contained cross-reactive epitopes (30,31). We therefore deleted the C terminus of DV NS1 protein from aa 271 to 352 (⌬C NS1) ( Fig.…”
Section: Abs Against DV Ns1 Lacking C Terminus Show Lower Binding Actmentioning
confidence: 99%
“…Given the pathological effects reported for anti-NS1 Abs, the underlying mechanisms need to be characterized and the relevant epitopes identified. Considerable progress toward these goals has been achieved (30,(65)(66)(67)(68), raising the hope that safer NS1 candidate vaccines may be developed with modified or deleted harmful epitopes such as those involved in autoimmune responses.…”
Section: Discussionmentioning
confidence: 99%